2020
DOI: 10.1016/s2542-5196(20)30059-0
|View full text |Cite
|
Sign up to set email alerts
|

Metal mining and birth defects: a case-control study in Lubumbashi, Democratic Republic of the Congo

Abstract: Background Widespread environmental contamination caused by mining of copper and cobalt has led to concerns about the possible association between birth defects and exposure to several toxic metals in southern Katanga, Democratic Republic of the Congo (DRC). We therefore aimed to assess the possible contribution of parental and antenatal exposure to trace metals to the occurrence of visible birth defects among neonates. Methods We did a case-control study between March 1, 2013, and Feb 28, 2015, in Lubumbashi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 41 publications
4
29
1
Order By: Relevance
“…The concentrations of trace metals in cord blood are shown in Supplement (2). The concentrations of Co, As, Cd, and U were markedly higher than those found in cord blood of the 60 controls infants of our case–control study (Van Brusselen et al, 2020); in contrast, the concentrations of Mn, Cu, Pb, and Zn were much lower.…”
Section: Resultscontrasting
confidence: 71%
See 4 more Smart Citations
“…The concentrations of trace metals in cord blood are shown in Supplement (2). The concentrations of Co, As, Cd, and U were markedly higher than those found in cord blood of the 60 controls infants of our case–control study (Van Brusselen et al, 2020); in contrast, the concentrations of Mn, Cu, Pb, and Zn were much lower.…”
Section: Resultscontrasting
confidence: 71%
“…First, the father of the affected child had worked as an artisanal mineworker around the time of conception. Biomonitoring studies have documented high burdens of various toxic metals in artisanal mineworkers in the area (Nemery & Banza Lubaba Nkulu, 2018), and in our case–control study of 138 neonates with visible birth defects and 108 normal neonates, all born in Lubumbashi, we demonstrated that paternal work in mining‐related jobs was an independent, strong and significant risk factor for fathering a child with a congenital malformation (Van Brusselen et al, 2020). We speculate that occupational exposure to toxic metals causes epigenetic alterations in men, thus possibly leading to malformations in their offspring (Baccarelli & Bollati, 2009).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations